ANALISIS PENGARUH DIGITAL MARKETING, ONLINE CUSTOMER EXPERIENCE QUALITY, E-SERVQUAL,TERHADAP ONLINE CUSTOMER TRUST, ONLINE CUSTOMER REVIEW RATING, DAN ONLINE CUSTOMER LOYALTY UMKM INDONESIA MASA PANDEMI COVID-19 - Maria Mia Kristanti (Widyagama National Conference on Economics and Business (WNCEB), 2021)
AbstrakLoyalitas pelanggan ditengah tingginya persaingan,menciptakan hubungan yang erat dengan pelanggan. Perkembangan dunia usaha menuntut usaha untuk menawarkan produk lebih inovatif melalui digital marketing. Urgensi maksimalisai online customer loyalty diperlukan.Tingginya word of mouth sharing, yang menceritakan online customer experience quality, online customer rating review pelanggan lainnya, mempengaruhi online customer trust, yang ditopang dengan online service quality yang bersimpati kepada pelanggan selama pandemi. Hasil purposive sampling 750 responden secara kuantitatif dengan SEM, alat analisis LISREL, menunjukkan bahwa Digital Marketing berdampak besar pada Online Customer Trust, yang berimplikasi pada Online Customer Trust serta Online Customer Review Rating, dengan ouput resistensi Online Customer Loyalty.Kata kunci: Digital Marketing, Online Customer Loyalty. AbstractCustomer loyalty in the midst of high competition, creating a close relationship with customers. The development of the business world requires efforts to offer more innovative products through digital marketing. The urgency of maximalisting online customer loyalty is required. The high word of mouth sharing, which tells the story of online customer experience quality, online customer rating reviews of other customers, affects online customer trust, which is supported by online service quality that is sympathetic to customers during pandemics. The results of purposive sampling of 750 respondents quantitatively with SEM, LISREL's analysis tool, showed that Digital Marketing has a major impact on Online Customer Trust, which has implications for Online Customer Trust as well as Online Customer Review Rating, with the support of Online Customer Loyalty.Keywords: Digital Marketing, Online Customer Loyalty